Topographical Distribution of Epileptogenic Tubers in Patients With Tuberous Sclerosis Complex. (April 2016) - Ellingson, Benjamin M.; Hirata, Yoko; Yogi, Akira; Karavaeva, Elena; Leu, Kevin; Woodworth, Davis C.; Harris, Robert J.; Enzmann, Dieter R.; Wu, Joyce Y.; Mathern, Gary W.; Salamon, Noriko
Tuberous sclerosis complex is a multisystem genetic syndrome often affecting the central nervous system. The purpose of the current study was to identify topographical patterns in the distribution specific to epileptogenic (n = 37) and nonepileptogenic (n = 544) tubers throughout the brain for a cohort of 23 tuberous sclerosis complex patients with a history of seizures. Tubers localized to the inferior parietal lobes, middle frontal lobes, middle temporal lobes, or central sulcus regions were associated with a high frequency of epileptogenic tubers. Epileptogenic tubers occurred statistically more frequently within the inferior parietal lobe and within the central sulcus region in children younger than 1 or between 1 and 3 years old, respectively. Results imply seizure activity in tuberous sclerosis complex patients can be associated with the location of cortical tubers.